Reconceptualizing Educational Information Management for Strategic Reform in Primary Education - Endi Rochaendi; Ahmad Salim; Nur Kholik; Ahmad Syamsul Arifin; Dyahsih Alin Sholihah (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study critically examines the strategic function of Educational Information Management (EIM) in transforming elementary education, situating it within the evolving paradigm of digital governance and equity-oriented educational reform. Employing a rigorous, systematic qualitative literature review methodology—reviewing peer-reviewed studies from 2015 to 2024 and relevant policy documents—the research synthesizes contemporary scholarly discourse, empirical evidence, and policy frameworks to elucidate how EIM catalyzes adaptive instructional design, inclusive decision-making processes, and data-informed leadership. The analysis reveals key findings: EIM has undergone a substantial conceptual shift from a static administrative system to a dynamic, integrative infrastructure that facilitates real-time data acquisition, personalized learning pathways, and participatory school governance. In particular, EIM demonstrably enhances institutional responsiveness, democratizes school–home communication, and strengthens collaborative engagement among educational stakeholders at the elementary school level. However, the findings also foreground persistent structural barriers, including disparities in digital infrastructure and insufficient educator digital competence, which continue to hinder the equitable implementation of EIM. The study concludes that realizing EIM’s transformative potential requires a holistic policy orientation integrating systemic digital capacity-building, ethically grounded design principles, and sustained public investment. Accordingly, EIM is rearticulated not merely as a technological apparatus but as a strategic and epistemological architecture that can directly inform policy and practice for building more inclusive, innovative, and coherent 21st-century elementary education systems.